Experimental Study of Mitigation of Wind-Induced Vibration in Asymmetric Cable-Stayed Bridge Using Sharp Wind Fairings - Guohui Zhao; Zhichao Wang; Shuo Zhu; Jianming Hao; Jun Wang (Applied Sciences, 2021)
This paper investigated the aerodynamic response features of an asymmetric cable-stayed bridge. The wind resistance design parameters for judging the response were first determined, afterwards the bridge dynamic characteristics were analyzed for subsequent aerodynamic analysis. The vortex-induced vibrations (VIV) and flutter response at various wind fairing angles were then examined by using a 1:50 sectional model in the wind tunnel test. Finally, a 1:150 full bridge aeroelastic model was employed to explore the aerodynamic stability and characteristics of the whole asymmetric bridge under different wind attack angles in various flow fields. The results show that the sharp wind fairings could reduce the VIV amplitude of the steel box girder cable-stayed bridge to some extent, and the example bridge has examined to have enough flutter stability through sectional and full bridge aeroelastic model wind tunnel tests. Unlike symmetric bridges, the bridge’s maximum displacement of first torsion mode shape is at the closure rather than the mid-span, which is the essential reason to lead this unique vibration feature. The results from the present study could highlight the important effect of structural asymmetry and fairing shape to the wind-induced bridge vibration and hence may facilitate more appropriate wind design of asymmetric cable-stayed bridges.